DA'WAH MANAGEMENT ON RELIGIOUS MODERATION BY THE INDONESIAN ULEMA COUNCIL IN DELI SERDANG REGENCY - Nasution, Wina Warohmah; Efendi, Erwan (Department of Research and Community Service at the Ummul Quro Al-Islami Bogor Institute, 2025)
The purpose of this study is to find out the da'wah planning carried out by the MUI Deli Serdang Regency on religious moderation. A descriptive qualitative methodology is used in this study. Data collection techniques are carried out through in-depth interviews, observations, and documentation. The results of the study show that the management of MUI da'wah is carried out through the stages of planning da'wah programs, organizing dai and materials, mapping the level of understanding of the community and religious leaders on the concept of religious moderation, implementing activities such as Ramadan safari and faith development in minority areas, and evaluation through follow-up visits to the assisted areas. MUI also innovates by using social media and radio to expand the reach of da'wah